Periodontitis as a Risk Factor for Rheumatoid Arthritis: a Matched-Cohort Study - Yoon Young Choi; Kyeong Hee Lee (Elsevier, 2021)
Objective: The intent was to analyse the association of periodontitis with the development of rheumatoid arthritis (RA) using a representative population-based cohort and longitudinal matched-cohort design. Methods: Participants were 40 years of age or older and had not been diagnosed with RA between 2002 and 2006. Among the participants, those who were newly diagnosed with periodontitis between 2004 and 2006 (excluding cases that had already been diagnosed with periodontitis between 2002 and 2003) were allotted to the periodontitis group. Among the participants, those who had never been diagnosed with periodontitis between 2002 and 2006 formed the control group, matched by sex, age, and household income at a 1:1 ratio. From 2007 to 2018, the 2 groups (n = 691,506) were followed to monitor the development of RA. The t-test and χ2 test compared the general characteristics and health-related variables of both groups. The Kaplan-Meier method with a log-rank test was conducted to compare the incidence of RA in both groups. The hazard ratio (HR) and adjusted hazard ratio (aHR) were calculated using a Cox proportional hazard regression analysis to evaluate the risk of subsequent RA. Results: Univariate analysis revealed that the periodontitis group was more likely to develop RA than the control group (hazard ratio 1.10), and multivariate analysis also revealed a higher incidence risk of RA (adjusted hazard ratio 1.09) in the periodontitis group. Conclusions: Our findings demonstrate that periodontitis is associated with an increased risk of developing RA.